Shariah Audit for Islamic Financial Services: The Needs and Challenges - Abdul Rahman, A. R. (Universiti Sains Islam Malaysia, 2024)
Institutions that offer Islamic financial services are expected to operate by the code of Islamic ethics and must function within the limits of shari’ah. In order to ensure that the operations of Islamic financial institutions do not contradict with shari’ah, the Shari’ah Advisory Council (SAC), Shari’ah Supervisory Board (SSB) or Shari’ah Supervisory Committee (SSC) normally functions as advisors or supervisors of Islamic banking activities. Internationally, the Accounting and Auditing Organizations of Islamic Financial Institutions (AAOIFI) and the Islamic Financial Services Board (IFSB) have issued a number of governance standards and guidelines. In Malaysia, Bank Negara Malaysia (BNM) has also issued the relevant guidelines to ensure prudent regulation of shari’ah matters in Islamic financial institutions. The main objective of this paper is to evaluate the need for shari’ah audit in order to complement the shari’ah compliance mechanisms that are already in place. Shari’ah audit must be undertaken systematically as part of the corporate governance mechanism of the Islamic Financial Institutions (IFIs). This is due to the increasing demands of stakeholders that require assurance of shari’ah compliance and accountability. The paper also discusses some challenges as pre-requisites to effectively undertake shari’ah audit.